Perforating pedicle flap in helix for large joints reconstruction in burns sequelae. - Pontón Ramón, Gabriela (2020)
Objectives: To describe the reconstructive possibilities offered by the use of propeller flap when it gives off a post-burn scar contracture in the large joints with functional limitation. Patients and methods: a prospective review was carried out with a sample for convenience in patients with burns sequelae that involve large joints and who were treated with a perforating pedicle flap between the period of a year (2018-2019) at HECAM. Results: The series included six patients; four men and two women around 5 to six years old with a median of 29 years and burn sequelae. A case with surgical site infection and six without complications. The surgery lasted around 120 to 170 min, the period of hospitalization had a median of 19 days (range: 6 to 55 days). The diameter of the flap was around 24cm2 to 84cm2, with different designs lobed (one case), bilobed (three cases), tetralobed (two cases); allowing the secondary defect to close directly in five of the cases and in one of them skin graft was necessary. Discussion: The presence of retractable scars and limitation of functionality of large joints constitutes an important sequel in the recovery of the burned patient who with the advances in knowledge has developed propeller flaps that preserves the underlying muscle provides a lower morbidity of the donor site, preserve functionality and reduce hospitalization time. Conclusion: the propeller flap improves retractions in the large joints returning the range of mobility. Recommendations: the propeller flap should be performed with a preoperative design with a transducer, considering the design, shape, and rotational movement in relation to variables such as the size of the defect and exposed structures.